STUDY OF UTILIZATION OF MAGNETIC ACTIVATED CARBON AS ALTERNATIVE SUBSTITUTION FOR ACTIVATED CARBON IN CARBON IN-LEACH SYSTEM AT UBPE PONGKOR - PT ANTAM (PERSERO) TBK - KURNIADANI (NIM : 22109306), HAMZAH
Processing of gold ore in the Gold Mining Business Unit Pongkor - PT Antam (Persero) Tbk through the stages of crushing, grinding, cyanidation, adsorption, elution, elektrowining, and smelting. Adsorption process is performed by using carbon in leach (CIL) method in which activated carbon is used as adsorbent. Size decreasing of the activated carbon could potentially occur due to activities in the CIL system which includes pumping, mixing, and filtration. Small-sized activated carbon will be reported to the tailings due to their size to pass through the screen in carbon screening process. Not only the loss of carbon from the system, but also the precious metals adsorbed on the carbon will also lost to the tailing. One of the efforts in reducing this risk is by modifying magnetic properties of carbon and then transport system of carbon between the tanks. In this research, magnetic activated carbon (MAC) was made from the activated carbon used at UBPE Pongkor. There are two types of activated carbon used i.e. pellets and granules. Magnetite (Fe3O4) synthetic was used to change the magnetic properties of the activated carbon. MAC-making process was performed by a co-precipitation impregnation process namely the formation and deposition of Fe3O4 occurs in the pores of the activated carbon. Precursors FeCl3 and FeSO4.7H2O were used in forming the Fe3O4 synthetic. Both of these precursors were mixed in a ratio of 2: 1 at 70 oC, then pH of this solution was increased by addition of NaOH. Precursor composition was set from 0.00625 to 0.2 mole for the FeCl3 and 0.003125 to 0.1 mole for FeSO4.7H2O. Based on this composition, six types of MAC was produced. Adsorption abilities of MAC were tested in the gold standard solution by using an electromagnetic device. The results showed that more than 50% of MAC-3 (0.025 mol FeCl3 and 0.0125 mol FeSO4.7H2O) of pellet and granular types can be recovered from the slurry by the electromagnetic device. The MAC-3 adsorption ability decreased down to 60% compared to the activated carbon. Characterization test was also carried out to see the difference of activated carbon, MAC and MAC-Au characteristics. The results showed that in general, activated carbon changed into MAC could be used as adsorbent material and it is possible to be used in the carbon in leach system at UBPE Pongkor - PT Antam (Persero) Tbk. Adjustment for implementation in operational conditions was needed to get the best properties of MAC.